Exploring Prevalence and Sociodemographic Factors Associated With Smoking Among Malaysian Adults: A Cross‐ Sectional Study - Mohd Hasni Ja'afar; Rosnah Ismail; Zaleha Md Isa; Azmi Mohd Tamil; Noor Hassim Ismail; Nafiza Mat Nasir; Nik Munirah Nasir; Nurul Hafiza Ab Razak; Najihah Zainol Abidin; Andrew Mente; Khairul Hazdi Yusof (Health Science Reports)
ABSTRACT Background and Aims The Malaysian government has implemented various antismoking measures to reduce the incidence of unhealthy lifestyles within the population. This study analyzes the baseline data of the Prospective Urban Rural Epidemiology (PURE) study to establish the prevalence of sociodemographic factors that are associated with smoking habits among Malaysian adults. Methods This study was carried out in urban and rural communities with adults aged between 35 and 70 years using purposive sampling. Standardized questionnaires were used to assess the smoking status and sociodemographic data of the participants. Bivariate analysis and multiple logistic regression were done to determine the association between smoking status and demographic characteristics among Malaysian adults. Results The prevalence of smoking among adults is 23.2%. The sociodemographic factors significantly associated with active smoking status were being a younger adult (adjusted odds ratio [AOR] = 1.26, 95% CI: 1.06–1.50), being male (AOR = 24.16, 95% CI: 20.58–28.36), being Malay (AOR = 1.72, 95% CI: 1.49–1.98), being a blue‐collar worker (AOR = 1.75, 95% CI: 1.48–2.06), having no formal education (AOR = 1.99, 95% CI: 1.56–2.53), being unmarried (AOR = 1.22, 95% CI: 1.02–1.48) and being of low socioeconomic status (AOR = 1.45, 95% CI: 1.14–1.84). Conclusion Public health policies and actions on smoking reduction should emphasize those identified as high‐risk sub‐populations, particularly younger adults, males and those who are not yet married, have no formal education and are of low socioeconomic status.